THE ROLE OF EXPLAINABLE ARTIFICIAL INTELLIGENCE IN INCREASING TRUST IN AUTONOMOUS SYSTEMS - Farid W (Penelitian dan Pengembangan Ilmu, 2025)
The rapid development of autonomous systems across various sectors highlights the importance of building user trust, particularly given the